Tana Ikuaka iyamuki: la corporización kukama entre geoontologías en la Amazonía peruana - Moreira, Daniel Fernandes (2024)
The anthropological study reveals epistemology of the kukama narratives, showing a nation with great sensitivity to transmit the functioning of its ways of life. In this intertwining, humans, no-humans and extra humans configure everyday life, in such a way that each people configures an ontology, because they have the kakura position. So we have lives that originate and position, circulate, familiarize and transform in the worlds. Consequently, the kukama, tuyuca, land is already turned over. This is the implications of the kukama’s daily lifestyle. The kukama narratives tell us that they think, eat and make life decisions with their hearts. For a clearer meaning of their actions, they also believe in dreams. From dreams it is possible to talk to drowned people who live in underwater worlds. So in this enchanted word, the lakes represent human ears, the trees the human eardrum and the cassava (Manihot esculenta) the human arms and legs. All of this forms the kukama corporatization. Archaeological ceramics are brought by the karuaras, the people who live below the water´s surface. The ceramics are placed in terrestrial spaces. Then we perceive a double human and no-human archeology that allows us to think that entities exist between geoontologies. The arrival of the colonizers has consequences in the social configuration because the initial kakura position is changed we have new forms of life that were not presented before such as: The bull, the ghost boat, the cell phone towers and the motorcycles that kill people in the city. Finally, there is a symbolic ecology composed of complex systems that are governed by entities that are between geoontologies in the Peruvian Amazon